Assessing Lupus‐Like Disease in Murine Model Systems. Issue 11 (8th November 2021) - Lee, Hui Yin; Celhar, Teja; Fairhurst, Anna‐Marie
Abstract: Systemic Lupus Erythematosus (SLE) is a complex and heterogenous autoimmune disease, where genetics, immunology, and environmental factors all play a role. Murine models have contributed critical information on mechanisms of disease and prospective therapeutics. The key features that have been used to study the disease include the development of anti‐nuclear autoantibodies (ANAs), splenomegaly, and kidney disease. The loss of tolerance and subsequent autoimmune features, and the progression to severe disease, are all dependent on immune dysregulation. In this article, we will describe the methods used to evaluate the underlying immunological features of the disease, as a more sensitive strategy to understand the disease itself and the mechanisms of potential novel therapeutics. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : End study protocols for tissue harvesting Basic Protocol 2 : End study protocols for tissue processing Basic Protocol 3 : Immunophenotyping using flow cytometry protocols Support Protocol : Tissue processing for cold storage Basic Protocol 4 : Additional tissue processing for later analyses Basic Protocol 5 : Analysis of serum auto‐antibodies by ELISAs (ANAs, snRNP, and dsDNA)